Rancang Bangun Sensor Deteksi Gizi Berdasarkan Standar Atropometri Anak - Maknunah, Lu'lu'ul; Ulum, Miftachul; Sukri, Hanifudin (Rekayasa, 2023)
In general, children's growth is monitored through Posyandu activities. This Posyandu seeks to monitor the growth and development of children so they do not experience malnutrition or malnutrition. One of the main factors in the process of physical growth and development is nutrition. However, the problem facing Posyandu today is the infrastructure used, namely measurement tools that still use conventional tools. This certainly affects the efficiency of parents in monitoring the growth and development of children, therefore this study designed a nutritional detection system for infants. The working principle of this tool utilizes an ultrasonic sensor to determine the baby's length and a load cell sensor to determine the baby's weight. The data detected by the two sensors will be processed using the stm32 microcontroller. By using the nutritional z-score formula, it can be classified into several statuses based on child anthropometric standards. Processed data will be displayed on the LCD and then stored in the MySQL database to make it easier to read the measurement results. In this study the test was carried out 10 times with different respondents. The data obtained from testing the design tool is compared with the measurement results on conventional tools so that an error is obtained on the weight sensor (load cell) of 3.3% and a success rate of 96.7%, the average percentage error on the height sensor (ultrasonic ) of 0.3% and a success rate of 99.7%.